Marine Cultural Tourism in Bali: A Study of The Interplay Between Marine and Cultural Attractions - Irene Hanna H. Sihombing; Ni Made Suastini (Politeknik Pariwisata Makassar, 2024)
This study explores the concept of marine and cultural tourism in Bali, focusing on the interplay between marine and cultural attractions. Bali, known for its rich cultural heritage and stunning marine environments, offers a unique blend of cultural and marine tourism experiences. This paper aims to analyze the potential of maritime cultural tourism in Bali and its contribution to sustainable tourism development. The study employs a qualitative research methodology, incorporating secondary data sources. The findings highlight the importance of integrating marine and cultural attractions to create a comprehensive and sustainable tourism strategy for Bali. The study concludes that marine and cultural tourism can be a vital component in Bali's tourism industry, enhancing the island's cultural and environmental sustainability.